Clinical and Basic Research on Renshen Yangrong Decoction - Sheng, Wei; Wang, Yun; Li, Jiang-Bo; Xu, Hua-Shan (Frontiers in Nutrition, 2019)
Renshen Yangrong Decotion is originally used for the treatment ofasthenic symptoms, such as exhaustion and asthenic disease, Qi and Blood deficiency disease etc, in recent years, it not only can promote hematopoietic function and improve immune function, but also can be used for the treatment of coronary heart disease, diabetic complications, malignant tumor, brain injury, and has satisfactory curative effect on sleep and fatigue. This textgives an overview that is Renshen Yangrong Decotion on fundamental research of hematopoietic function and improved immune function and the status of clinical research on theabove diseases in recent years.